The Advantage Of Combined Machine Technology That Prepares The Soil For Planting Poly Crops Under A Closed Tunnel Film (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article presents the technology of the combined machine that prepares the soil for high-quality cultivation of rice crops under a closed tunnel film, and the quality treatment of the soil for preparing seedlings for planting.